2011
DOI: 10.3109/0886022x.2011.574767
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects ofN-Acetylcysteine and Ebselen on Renal Ischemia/Reperfusion Injury

Abstract: Introduction: It has been demonstrated that peroxynitrite accompanies acute renal ischemia and contributes to the pathophysiology of renal damage. Therefore, we aimed to investigate the roles of N-acetylcysteine (NAC), a well-known powerful antioxidant, and ebselen (E), a scavenger of peroxynitrite, on renal injury induced by renal ischemia/reperfusion injury (IRI) of rat kidney. Materials and methods: Forty male Sprague-Dawley rats were divided into five groups: sham, renal IRI, renal IRI+NAC, renal IRI+E, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Ebselen is an antioxidant that scavenges peroxynitrite without effecting endogenous nitric oxide (195), making this antioxidant very attractive for treatment of oxidative stress-related pathological conditions. In various animal models of AKI, ebselen application prevented lipid peroxidation, enhanced endothelial and epithelial cell viability, and improved renal function (35,39,58,94,150,207,223,228). However, the benefits of ebselen remain to be seen in human subjects.…”
Section: Edaravone and Ebselenmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebselen is an antioxidant that scavenges peroxynitrite without effecting endogenous nitric oxide (195), making this antioxidant very attractive for treatment of oxidative stress-related pathological conditions. In various animal models of AKI, ebselen application prevented lipid peroxidation, enhanced endothelial and epithelial cell viability, and improved renal function (35,39,58,94,150,207,223,228). However, the benefits of ebselen remain to be seen in human subjects.…”
Section: Edaravone and Ebselenmentioning
confidence: 99%
“…Other compounds that target the mitochondria have gained interest in recent years for treatment of kidney injury and disease, including mitoquinone mesylate (a derivative of CoQ10, termed MitoQ) and a-tocopherol-conjugated triphenylphosphonium (otherwise referred to as MitoVit E or mitochondrial targeted vitamin E). Animal studies with MitoQ have shown its ability to improve renal function during diabetic nephropathy, toxin-induced nephropathy, and IRI-induced AKI (34, 58,150,223). However, it remains to be seen if MitoQ improves renal function in human CKD patients.…”
Section: Mitochondrial Antioxidantsmentioning
confidence: 99%
“…All of these hazardous events can lead to undesirable conditions, including hypertension and renal failure [11]. Although, several antioxidants and anti-inflammatory agents have been used to prevent or decrease the kidney damage that can be caused by I/R injury [12][13][14][15], there have been no studies on the protective and therapeutic effects of dexpanthenol (Dxp) against renal I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Restoration of blood flow after a period of ischemia may further increase the initial damage via release of oxygen free radicals [reactive oxygen species (ROS)]. 2 Free radicals react with almost all biomolecules including nucleic acids, proteins, lipids, carbohydrates, and connective tissue macromolecules and cause reversible or irreversible changes in the structure of these molecules. 3 While small amounts of free radicals are formed during ischemia, much larger amounts are formed in the reperfusion period.…”
Section: Introductionmentioning
confidence: 99%
“…4 Free radical scavengers are one of the main focuses of current ischemia/reperfusion (I/R) research, but an effective treatment ready to use in routine practice has not been found yet. 2,5,6 Hyperbaric oxygen (HBO) therapy involves the intermittent inhalation of 100% of oxygen under a pressure greater than 1 atm. HBO therapy increases the dissolved oxygen concentration in the arterial blood and enhances the rate of diffusion of oxygen into poorly perfused tissues.…”
Section: Introductionmentioning
confidence: 99%